2020
DOI: 10.1016/j.imu.2020.100432
|View full text |Cite
|
Sign up to set email alerts
|

Digitalization plan in medical education during COVID-19 lockdown

Abstract: Background The COVID-19 pandemic has enhanced the adoption of virtual learning after the urgent suspension of traditional teaching. Different online learning strategies were established to face this learning crisis. The present descriptive cross-sectional study was conducted to reveal the different digital procedures implemented by the College of Medicine at Qassim University for better student performance and achievement. Methods The switch into distance-based learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
95
0
11

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(110 citation statements)
references
References 17 publications
4
95
0
11
Order By: Relevance
“…Overall, there was a significant transition from in‐person lecture delivery to not in‐person lecture delivery during Covid‐19. These results align with the findings published by Alkhowailed et al (2020), Cuschieri and Calleja (2020), Ferrel and Ryan (2020), Herr and Nelson (2020), Longhurst et al (2020), Naidoo et al (2020), and Pather et al (2020). Collectively, these changes reflect the national (Mervosh et al, 2020; NASHP, 2020) and international (Schramm and Melin, 2020) stay‐at‐home and physical distancing requirements, where large cohorts of learners physically present in a classroom, lecture hall, and/or laboratory setting would not be permitted.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Overall, there was a significant transition from in‐person lecture delivery to not in‐person lecture delivery during Covid‐19. These results align with the findings published by Alkhowailed et al (2020), Cuschieri and Calleja (2020), Ferrel and Ryan (2020), Herr and Nelson (2020), Longhurst et al (2020), Naidoo et al (2020), and Pather et al (2020). Collectively, these changes reflect the national (Mervosh et al, 2020; NASHP, 2020) and international (Schramm and Melin, 2020) stay‐at‐home and physical distancing requirements, where large cohorts of learners physically present in a classroom, lecture hall, and/or laboratory setting would not be permitted.…”
Section: Discussionsupporting
confidence: 92%
“…The rapid pace with which the pandemic spread across the world required school closures that led programs to reassess their curricula. Changes included implementing an online problem‐based learning (PBL) curriculum (Alkhowailed et al, 2020) and modifications to the traditional medical student mentoring model (Kazerooni et al, 2020), admissions processes (Murphy, 2020), clinical experiences (Theoret and Ming, 2020; Wang et al, 2020; Weiner, 2020), and early graduation to aid in treating Covid‐19 patients (NYU, 2020; Wang et al, 2020). In addition, institutions had to transition a large number of lectures from in‐person to pre‐recorded lectures and canceled interactive small group sessions (Ferrel and Ryan, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…There was an increase in participation for e-learning through webinars during the pandemic among the neurorehabilitation professionals. Carrying on this culture in the future to digitalize medical education, will be beneficial to the students and the staff as well, and it has been well accepted at present due to the current scenario ( 25 ). As reported in a few studies, e-learning has its own merits and demerits, it can be concluded that although traditional learning cannot be replaced by e-learning but adjusting and accepting the new normal is the way forward ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Arandjelovic et al [21] in a thorough study review the strategies implemented during previous global infectious disease epidemics, and suggest strategies for utilizing clinical education in times of pandemic crisis. Similar discussion and arguments for the support of medical education with e-learning can be found in [22], [23] with emphasis in multimodal multi-Institutional solution to remote medical student education and Digitalization or strategic consideration of key issues like the Strategic Deployment of Cardiology Fellows in Training Using the Accreditation Council for Graduate Medical Education Coronavirus Disease [24].…”
Section: Introductionmentioning
confidence: 90%